Pregnancy Is Associated with Impaired Transcription of Human Endogenous Retroviruses and of TRIM28 and SETDB1, Particularly in Mothers Affected by Multiple Sclerosis - Tovo, Pier-Angelo; Marozio, Luca; Abbona, Giancarlo; Calvi, Cristina; Frezet, Federica; Gambarino, Stefano; Dini, Maddalena; Benedetto, Chiara; Galliano, Ilaria; Bergallo, Massimiliano (Viruses, 2023)
Accumulating evidence highlights the pathogenetic role of human endogenous retroviruses (HERVs) in eliciting and maintaining multiple sclerosis (MS). Epigenetic mechanisms, such as those regulated by TRIM 28 and SETDB1, are implicated in HERV activation and in neuroinflammatory disorders, including MS. Pregnancy markedly improves the course of MS, but no study explored the expressions of HERVs and of TRIM28 and SETDB1 during gestation. Using a polymerase chain reaction real-time Taqman amplification assay, we assessed and compared the transcriptional levels of pol genes of HERV-H, HERV-K, HERV-W; of env genes of Syncytin (SYN)1, SYN2, and multiple sclerosis associated retrovirus (MSRV); and of TRIM28 and SETDB1 in peripheral blood and placenta from 20 mothers affected by MS; from 27 healthy mothers, in cord blood from their neonates; and in blood from healthy women of child-bearing age. The HERV mRNA levels were significantly lower in pregnant than in nonpregnant women. Expressions of all HERVs were downregulated in the chorion and in the decidua basalis of MS mothers compared to healthy mothers. The former also showed lower mRNA levels of HERV-K-pol and of SYN1, SYN2, and MSRV in peripheral blood. Significantly lower expressions of TRIM28 and SETDB1 also emerged in pregnant vs. nonpregnant women and in blood, chorion, and decidua of mothers with MS vs. healthy mothers. In contrast, HERV and TRIM28/SETDB1 expressions were comparable between their neonates. These results show that gestation is characterized by impaired expressions of HERVs and TRIM28/SETDB1, particularly in mothers with MS. Given the beneficial effects of pregnancy on MS and the wealth of data suggesting the putative contribution of HERVs and epigenetic processes in the pathogenesis of the disease, our findings may further support innovative therapeutic interventions to block HERV activation and to control aberrant epigenetic pathways in MS-affected patients.